Experimental Research on Compressive and Shrinkage Properties of ECC Containing Ceramic Wastes Under Different Curing Conditions - Xiong, Yan; Yang, Yi; Fang, Shuai; Wu, Di; Tang, Yingfeng (Frontiers in Materials, 2021)
Engineered cementitious composite (ECC) suffers from high shrinkage and low early strength due to large dosage of cementitious materials and slow hydration of fly ash. This study aims to improve compressive properties and reduce drying shrinkage of ECC using ceramic wastes and hydrothermal curing. Experimental results have indicated that ceramic polishing powder (CPP) and recycled ceramic sand (RCS) exert opposite effect on the compressive strength of ECC. Hydrothermal cured ECC enhances elasticity modulus and compressive strength, and reduces later drying shrinkage as compared with that under standard curing. A CPP dosage of 35% and a hydrothermal curing regime with a temperature of 70 ℃ and age of seven days are recommended for engineering application of ECC.